PERFORMANCE EVALUATION OF EMPLOYEES IN SUMMIT OTO FINANCE SEMARANG - Ahmad Budiono; Aprih Santoso (Politeknik Negeri Batam, 2020)
The purpose of this study is to evaluate: (1) The effect of work discipline on employee performance. (2) The effect of transformational leadership on employee performance. (3) The effect of the work environment on employee performance at PT. Summit Oto Finance Semarang. The data analysis technique uses: validity test, reliability test, multiple linear regression analysis, and statistical tests (t test, F test and determinant coefficient). The population in this study is the entire population as a sample of 65 employees and using data collection techniques in the form of questionnaires. The results of this study indicate that: (1) Work discipline does not significantly effect on employee performance. (2) Transformational leadership has a significant effect on employee performance. (3) The work environment has a significant effect on employee’s performance of PT. Summit Oto Finance Semarang.